Mechanistic insights into traditional Chinese medicine for viral pneumonia treatment: signaling pathway perspectives - Zheng, Shihao; Xue, Tianyu; Li, Size; Qi, Wenying; Zao, Xiaobin; Zhang, Peng; Cheng, Fan-E; Ye, Yongan; Dong, Peipei (Frontiers in Pharmacology, 2025)
Since December 2019, the World Health Organization declared COVID-19 outbreak in the World as a highly contagious respiratory disease poses a significant challenge to the world. The main symptoms of patients are cough, fever, diarrhea, etc. In addition, the COVID-19 genome has strong plasticity, and there is a risk of cross-species transmission. The use of western medicine antibiotics brings good therapeutic effects, but also accompanied by many adverse reactions of physical and mental damage. At present, TCM has achieved remarkable results in the treatment of COVID-19. In addition to enriching the cognitive theories of traditional Chinese medicine in the treatment of COVID-19, studies on the cell signal transduction mechanism of TCM in the treatment of COVID-19 have developed rapidly from the perspective of molecular biology. Through literature search, it is found that the occurrence of COVID-19 is closely related to cellular inflammatory response, immune response, apoptosis, proliferation and other physiological and pathological processes. This study systematically elucidates the molecular mechanisms by which traditional Chinese medicine treats COVID-19 by regulating key signaling pathways such as PI3K/Akt, NF-κB, JAK/STAT, and mTOR. It not only effectively alleviates COVID-19 symptoms and suppresses pulmonary inflammation but also reduces complications and drug-related adverse reactions. The integrated traditional Chinese and Western medicine model demonstrates significant synergistic effects in antiviral treatment and overall regulation. Future research should further explore the cross-mechanisms of signaling pathways, strengthen evidence-based medical validation, promote the modernization of traditional Chinese medicine, and provide safer and more effective treatment strategies for global pandemic control.